PROBLEMATIKA PEDAGANG BUAH KAKI LIMA DI KOTA PALANGKA RAYA - Hakim, Sofyan; Sali, Sali; Alfauji, Akhmad (AL-QARDH, 2018)
The problem of fruit street vendors is because they open their trade use the part of fruit street or sidewalk and other places for public